Risk factor analysis for pneumococcal meningitis in adults with invasive pneumococcal infection - Burckhardt, Irene; Burckhardt, F.; Linden, Mark van der; Heeg, Corinna; Reinert, R. R. (Epidemiology and infection, 2010)
Pneumococcal meningitis is a subgroup of invasive pneumococcal disease with a case-fatality rate of up to 30% and long-term sequelae in more than 50% of cases in adults in developed countries. We aimed to determine risk factors for this particular form of pneumococcal disease. We conducted a prospective population-based laboratory study of invasive pneumococcal disease in adults in North-Rhine-Westphalia, Germany from February 2001 to August 2006. All isolates underwent serotyping and susceptibility testing at the National Reference Centre for Streptococci in Aachen, Germany. Data were analysed using multiple linear regression. A total of 1043 isolates from bacteraemia and 131 isolates from meningitis were included into the study. Serotype 23F and being female were independent risk factors for pneumococcal meningitis. Being ⩾60 years and serotype 1 were associated with a reduced odds ratio. Season, penicillin and macrolide resistance were not statistically associated with CNS involvement.
Gesehen am 16.03.2023